Exploring the Products from Pinewood Pyrolysis in Three Different Reactor Systems - Garrido-Lazo, R (American Chemical Society, 2015)
The product yields and selectivity from fast pyrolysis of biomass are highly dependent upon the physicochemical properties of the biomass feedstock and the process conditions. The objective of this study was to compare the product yields and selectivity from fast pyrolysis of pinewood using three different reactors systems typically used in research laboratory settings for studying biomass pyrolysis: a micropyrolyzer coupled to a gas chromatography/mass spectrometry system, a batch tubular reactor, and a fluidized-bed (FB) continuous reactor. The pyrolysis of pinewood using the three reactors gave different bio-oil yields, altered the amounts and compositions of the non-condensable gases, and gave rise to variations in the amount and types of chemicals in bio-oil produced. The variability in residence times of the three reactors and mechanical factors within the FB reactor altered the degree of secondary reactions of the primary pyrolysis vapor, leading to the observed changes in composition. Lower yields of carbohydrates were also found to be a consequence of these same intrinsic reactor design constraints. These findings shed significant light on how residence time and the mechanical properties of a reactor configuration affect the products of pyrolysis through the alteration of secondary pyrolytic reactions. © 2015 American Chemical Society.